STRATEGI GURU DALAM MENANAMKAN NILAI-NILAI RELIGIUS UNTUK MENINGKATKAN KUALITAS KEPRIBADIAN PESERTA DIDIK - Vivi Mar'atus Sholihah; Rosichin Mansur; Lia Nur Atiqoh Bela Dina (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
AbstrakTeacher strategy in planting religius value:(1) how the personality of students in instilling religious value (2) how the teacher's strategy in instilling the value of religious values to improve the personality quality of students (3) supporting factors and inhibiting factors in instilling religious values. location of this study at madrasah ibtidaiyah Raudlatul Ulum ngiji Malang. in this study the personality of students is very good at instilling religious value the strategy carried out in instilling this religion with moral practice, practice of aqidah, and practice of shari'ah. administering the value of aqeedah through Allah and his creation, introduce the book of the Qur'an, affecting apostles and angels. in instilling the Shari'ah values students are invited to pray together before the lesson begins and the Dhuha prayer in congregation. moral recognition, namely with morality to God, parents, teachers, friends and the surrounding community. supporting factors in instilling religious value, namely the motivation of the headmaster, cooperation with parents, facilities and infrastructure Keyword : strategy, value, relegius